Are population‐based patient‐reported outcomes associated with overall survival in patients with advanced pancreatic cancer?. (17th November 2019) - Dai, Wei Fang; Beca, Jaclyn; Guo, Helen; Isaranawatchai, Wanrudee; Schwartz, Deborah; Naipaul, Rohini; Arias, Jessica; Qiao, Yao; Gavura, Scott; Redmond‐Misner, Ruby; Ismail, Zahra; Barbera, Lisa; et al.
Abstract: Background: Advanced pancreatic cancer (APC) patients often have substantial symptom burden. In Ontario, patients routinely complete the Edmonton Symptom Assessment Scale (ESAS), which screens for nine symptoms (scale: 0‐10), in cancer clinics. We explored the association between baseline patient‐reported outcomes, via ESAS, and overall survival (OS). Methods: Advanced pancreatic cancer patients with ESAS records prior to receiving publicly funded drugs from November 2008 to March 2016 were retrospectively identified from Cancer Care Ontario's administrative databases. We examined three composite ESAS scores: total symptom distress score (TSDS: 9 symptoms), physical symptom score (PHS: 6/9 symptoms), and psychological symptom score (PSS: 2/9 symptoms); Composite scores greater than defined thresholds (TSDS ≥36, PHS ≥24, PSS ≥8) were considered as high symptom burden. Crude OS was assessed using Kaplan‐Meier method. Hazard ratios (HRs) were assessed using multivariable Cox models. Analysis was repeated in a sub‐cohort with Eastern Cooperative Oncology Group (ECOG) status and metastasis. Results: We identified 2199 APC patients (mean age 64 years, 55% male) with ESAS records prior to receiving chemotherapy. Crude median survival was 4.5 and 7.3 months for high and low TSDS, respectively. High TSDS was associated with lower OS (HR = 1.47, 95% CI: 1.33, 1.63). In the sub‐cohort (n = 393) with ECOG status and metastasis, high TSDS was also associated with lower OS (HR = 1.34, 95% CI: 1.04, 1.73). Similar trends were observed for PHS and PSS. Conclusions: Higher burden of patient‐reported outcome was associated with reduced OS among APC patients. The effect was prominent after adjusting for ECOG status. Abstract : In a cohort of advanced pancreatic cancer patients, we observed that higher burden of patient‐reported symptoms at baseline is associated with reduced overall survival. The association remained significant after accounting for performance status and type of treatment.